Nhìn lại vấn đề thuật ngữ và danh pháp hóa học hữu cơ ở nước ta trong hai năm qua - Trần, Quốc Sơn (Đại học Quốc gia Hà Nội, 2020)
This paper present a brief review on the use of nomenclature and terminology in organic chemistry during last two years. We would like to propose a solution to the unity in this domain at the present time.